Challenges of online learning amid the COVID-19: College students’ perspective - Xia, Yuefan; Hu, Yawen; Wu, Chenyi; Yang, Ling; Lei, Man (Frontiers in Psychology, 2022)
Universities in China’s transition to online education in response to the COVID-19 pandemic have spawned several research studies. However, studies exploring college students’ technological skills, relationships with their peers and instructors, and collaborative learning experiences during the pandemic are scarce. Three aspects were explored in this mixed study: (1) changes in students’ engagement in class and the main factors involved; (2) students’ feelings and reactions during online learning; and (3) how students related to their peers and instructors. Data were collected through a qualitative survey supplemented by quantitative data about students’ attitudes to online learning using the SAROL scale. This paper argues that online learning may not produce the desired results due to lack of interaction with instructors, no campus socialization or well-trained technology skills, and appropriate content for online courses and group work. The findings further revealed that online learning offers college students new ways to learn independently, collaborate and build relationships with their peers. It encourages them to reconsider ways to improve their technology skills, learning methods, communication skills and reconceptualize their responsibilities as team members.